RETRACTED: Several Chaotic Analysis of Lorenz System - Md. Shakhawat Alam; Payer Ahmed (European Scientific Journal, ESJ, 2017)
This paper has been retracted on 27.11.2021. The reasons for the retraction are included in the retraction notice available on this website.